Enseñanza para u cambio conceptual: ejemplos de fuerza y de movimiento - Hewson, P. W.; Beeth, M. E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this article the possibility of learning as a conceptual change and the way of teaching appropriate for this is discussed. This teaching has to have certain characteristics and ensure that the debate in the classroom is centered on the explicit ideas of the children, the status of which must be discussed and negotiated. To achieve this, the curriculum must give importance to the justification of ideas, the debate must be metacognitive and the role of the professor must be more active and diversified. One example of this way of teaching is presented in the article.